Pengembangan Modul Pembelajaran Kimia Berbasis Permasalahan Lingkungan dengan Pendekatan Problem Based Learning pad Materi Kelarutan dan Hasil Kali Kelarutan - Rahmawati, Dian; Purwanto, Agung; Rahman, Arif (LPPM Universitas Negeri Jakarta, 2019)
This study aims to develop a feasible chemistry learning media in the form of learning modules based on environmental problems with a problem-based learning approach on th solubility and the solubility product. The research method used is Research and Development (R&D). There are 4 stages carried out in this study, which are preliminary analysis, product planning and development, product validation by experts, and product trials on students and teachers. Learning modules are prepared by applying the problem-based learning approach. The presentation of problems and learning activities are systematically designed with an attractive appearance to increase students' interest in the learning process. The results of the module validation assessment from chemistry experts, linguists experts and media experts respectively showed very good results with the percentage, respectively 93.98%, 86.03% and 88.39%. The results of the module feasibility assessment trials by students get a very good interpretation with a percentage of 78.89% and the results of the module feasibility assessment trials by teacher also get a very good interpretation with a percentage of 96.83%. Based on the results obtained, it can be concluded that the chemistry learning module based on environmental problems with the problem-based learning approach on the solubility and the solubility product that has been developed is feasible and is suitable for use in the chemistry learning process in school. Keywords: Learning module, Problem Based Learning Approach, Environmental Based Chemistry, Solubility and Solubility Product